ADULT-ONSET STILL’S DISEASE: ASPECTS OF THE HEMATOLOGY CLINIC - M. M. Agakishiev; I. I. Mulina; A. M. Popova; I. N. Nechunaeva; L. M. Maslova; I. B. Kovynev; T. I. Pospelova (Сибирский научный медицинский журнал, 2019)
The analysis of literature data on modern approaches in the diagnosis and treatment of adult-onset Still’s disease has been performed. A clinical case of Still’s disease associated with lymphadenopathy syndrome was demonstrated. It is noted that the diagnosis of adult Still’s disease requires a doctor to exclude a complex of a tumor, rheumatological and infectious pathology. It is important for a hematologist not to miss a blood tumor and to prevent a diagnostic error. The authors showed the criteria for exclusion of myeloblastic hematosarcoma and malignant lymphoma in a patient with Still’s disease. The importance of taking into account the clinical data is noted: the absence of progressive sarcomal growth of lymph nodes, the lack of generalization and dissemination of myeloblastic substrate in the body, the reduction of fever with steroids and nonsteroidal anti-inflammatory drugs. The role of monitoring clinical and biochemical blood parameters has been proved such as: blood ferritin level, C-reactive protein, hemogram parameters. The relative value of positron emission computed tomography data, which can be falsely interpreted, is shown. Correct diagnosis, rejection of an incorrect diagnosis of hematological tumor will prevent the administration of myeloablative polychemotherapy, which is dangerous for an adult patient with Still’s disease. The article outlines the differential diagnosis algorithm, presents the criteria for diagnosis and approaches to therapy. A feature of the clinical case was the detection of antibodies against yersenia. A meeting with an infectious agent could be a trigger for the development of a multisystem form of Still’s disease in a patient.